PENGARUH KONSERVATISME AKUNTANSI PADA EFISIENSI INVESTASI DAN INOVASI - Nurul Qomariyah; Suwarno Suwarno (PROCEEDING UMSURABAYA, 2022)
ABSTRACT   The purpose of this study is to assess the role of conservatism on investment efficiency and firm innovation. Accounting conservatism is considered to reduce management's encouragement to invest in fixed assets that are not in accordance with opportunities. Innovation and conservatism seem to be contradictory concepts, innovation involves risk taking and invention, while conservatism embodies prudence and risk aversion. The sample used in this study were non-financial companies listed on the Indonesia Stock Exchange during 2019 using a purposive sampling technique. The data analysis method used is simple linear regression analysis. The empirical results of this study indicate that the accounting conservatism variable has no effect on investment efficiency. While the variable accounting conservatism has a significant effect on innovation.Keywords                   : Accounting Conservatism; Investment Efficiency; Innovation